x , y and z are positive reals satisfying x + y + z = 1 0 .
If the maximum value of x y z + x y + y z + z x can be expressed as B A , where A and B are coprime positive integers , find A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same way! :-)
I did the same way too.
We can solve the problem by breaking the expression into two parts x y z and x y + y z + z x and applying AM-GM inequality . Note that AM-GM inequality only applies if x , y , z > 0 , which is shown to be the case later.
x + y + z ⟹ x y z ≥ 3 3 x y z ≤ ( 3 x + y + z ) 3 = 2 7 1 0 0 0
Equality occurs when x = y = z = 3 1 0 > 0 .
x y + y z + z x ⟹ 2 3 ( x y + y z + z x ) ⟹ x y + y z + z x ≤ ( 2 x + y ) 2 + ( 2 y + z ) 2 + ( 2 z + x ) 2 ≤ 4 1 ( x 2 + 2 x y + y 2 + y 2 + 2 y z + z 2 + z 2 + 2 z x + x 2 ) ≤ 2 1 ( x 2 + y 2 + z 2 + x y + y z + z x ) ≤ 2 1 ( x 2 + y 2 + z 2 + 2 ( x y + y z + z x ) ) ≤ 2 1 ( x + y + z ) 2 = 5 0 ≤ 3 2 ⋅ 5 0 = 3 1 0 0
Equality again occurs when x = y = z = 3 1 0 . Therefore,
⟹ x y z + x y + y z + z x ≤ 2 7 1 0 0 0 + 3 1 0 0 = 2 7 1 9 0 0
⟹ A + Y = 1 9 0 0 + 2 7 = 1 9 2 7
I have a much simpler version for the maximum value of x y + y z + z x . By the Cauchy-Schwarz Inequality, we have, x 2 + y 2 + z 2 ≥ x y + y z + z x . Adding 2 ( x y + y z + z x ) to both sides, ( x + y + z ) 2 ≥ 3 ( x y + y z + z x ) . ⟹ x y + y z + z x ≤ 3 ( 1 0 ) 2 = 3 1 0 0 .
Due to this problem is a calculus problem and the other solutions are algebraic solutions, I'll give a calculus solution
Relevant wiki: Lagrange multipliers
Let L ( x , y , z ) = x y z + x y + y z + z x + λ ( x + y + z − 1 0 ) ⇒ d x d L ( x , y , z ) = y z + y + z + λ = 0 d y d L ( x , y , z ) = x z + x + z + λ = 0 d z d L ( x , y , z ) = y x + y + x + λ = 0 . Substituing λ in the previous equations, we get y z + y + z = x z + x + z = y x + y + x ⇒ x = y = z and substituing in x + y + z = 1 0 we get x = y = z = 3 1 0 .
We can see that the hessian matrix d 2 L ( 1 0 / 3 , 1 0 / 3 , 1 0 / 3 ) is a defined negative matrix(it's left to the reader as an exercise), so x y z + x y + y z + z x will have a maximum for x = y = z = 3 1 0 and this maximum is ( 3 1 0 ) 3 + 3 ( 3 1 0 ) 2 = 2 7 1 0 0 0 + 3 1 0 0 = 2 7 1 9 0 0 ...
Problem Loading...
Note Loading...
Set Loading...
Let us define new variables X = x + 1 , Y = y + 1 , Z = z + 1 to restate the problem as: Find the maximum value of ( X Y Z − 1 1 ) when X + Y + Z = 1 3 . Using A.M.-G.M. inequality, it works out to ( 3 1 3 ) 3 − 1 1 = 2 7 1 9 0 0 valid for positive values of the variables. Hence answer 1927.